RDE & dynamometer analysis of light-duty vehicle emissions across altitudes, temperatures, and driving styles - Jiguang Wang; Li Wang; Jiaqiang Li; Jianwei Li; Feng Xu; Fei Han; Jianliang He; Qiuling Chen; Xudong Chen (PLoS ONE, 2025)
This study aimed to investigate the impact of altitude, cold start, ambient temperatures, and driving behaviors on the Real Driving Emissions (RDE) of China VI standard light-duty gasoline vehicles. Tests were conducted on actual roads and in vehicle emission environment simulation laboratories at altitudes of 700 m, 1,300 m, 1,900 m, and 2,400 m in Yunnan. The results showed that: (1) as altitude increased, the CO emission factor exhibited a positive correlation trend, peaking at 2400 m with a 2.56-fold increase compared to 700 m. The NOX emission factor displayed an “N” distribution, with aggressive driving at 1900 m yielding 1.89 times higher emissions than normal driving and 3.02 times higher than low-temperature driving; (2) under low-temperature rotating wheel conditions, PN emission factors were 7.55 times higher than normal driving and 71.71 times higher than aggressive driving, indicating that driving behavior significantly influenced NOX emissions, while low-temperature environments had a greater impact on PN emissions; (3) compared to non-cold-start conditions, the cold-start phase increased urban CO, NOX, and PN emission factors by 4.72% to 225.00%, 0.19% to 15.38%, and 6.45% to 430.36%, respectively, with total emission factors increasing by 0.07% to 0.55%, 0.00% to 6.00%, and 1.03% to 242.64%.